Identification of and Hydrogen Peroxide Production by Fecal and Vaginal Lactobacilli Isolated from Japanese Women and Newborn Infants - Song, Yu-Li (American Society for Microbiology, 1999)
We identified Lactobacillus isolates from Japanese women and newborn infants by a DNA-DNA hybridization method. The predominating lactobacilli were Lactobacillus crispatus and Lactobacillus gasseri in the women’s vaginas and the newborns’ intestines and L. gasseri and Lactobacillus fermentum in the women’s intestines. All L. crispatus strains were exclusively strong H(2)O(2) producers.